The place of endobronchial interventional procedures and intratumoral chemotherapy in the therapeutic strategy of lung cancer - ÇELİKOĞLU, Firuz; PAPİLA, İrfan; Papila, Çiğdem; ÇELİKOĞLU, İ. Seyhan (Cerrahpaşa Medical Journal, 2014)
The clinical studies in the last decades have demonstrated that the obstruction in the proximal airways due to non-smallcell- lung-cancer influences a negative effect on the outcome of disease. Moreover the clinical studies have demonstrated that the alleviation of the obstruction in the airways by the available interventional bronchoscope procedures ameliorates the efficiency of the standard therapeutic modalities of lung cancer as well as the survival rates of patients. In this present paper the advantages and disadvantages of different interventional endobronchial therapeutic modalities in the treatment of endobronchial malignancies were reviewed. Especially the effectiveness of using different methods sequentially or concomitantly in the same patient is emphasized. The interventional endoscopic procedures were studied in two main groups: 1- Ablative destructive methods with non-specific effects on the tissue: a) thermic procedures, such as electrocautery, laser photoresection, argon- plasma coagulation, cryotherapy; b) mechanical procedures, such as piecemeal resection with forceps, dilatation with balloon catheter, installation a stent. 2- Procedures with specific effects, destroying exclusively the cancerous cells: brachytherapy, photodynamic therapy. In addition to these, the novel paradigm of endobronchial intratumoral chemotherapy was described as interventional therapeutic modalities with specific effect on malignant cells alike brachytherapy and photodynamic therapy. The potential synergistic efficiency of EITC when combined with standard lung cancer therapies, brachytherapy and with photodynamic therapy was discussed.